THE AMERICAN WOMAN IDENTITY AS REFLECTED IN EAT PRAY LOVE NOVEL IN HER PURSUIT OF HAPPINESS - Edi Ardian; Samsul Amri; Edi Susrianto Indra Putra (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2023)
American culture background influences the content of literary work in this novel. The purpose of the research is to know an American woman identity as reflected in Eat Pray Love (EPL) novel in her pursuit of happiness. For that purpose, a thematic and descriptive, analysis is conducted to answer two research problems: 1) what constraint of woman to face in her attempts to achieve happiness; and 2) How the novel reflects of the American woman identity in her pursuit of happiness? The analysis finds out that woman faces the problem based on her culture. She is unhappy in her marriage, but the she deal with her problem in American culture identity, she attempts individual redefinition of the self by undergoing material and spiritual search and fulfillment, and finally managed to achieve her true happiness. The ego wins over the superego, and a new identity comes out of an internal conflict and an intense spiritual process. American individualism allows this. American individualism gives greater priority to individuals.